Reactions of 3-aryl-1-(trifluoromethyl)prop-2-yn-1-iminium salts with 1,3-dienes and styrenes - Schneider, Thomas; Keim, Michael; Seitz, Bianca; Maas, Gerhard (Beilstein Journal of Organic Chemistry, 2020)
3-Aryl-1-(trifluoromethyl)prop-2-yn-1-iminium triflate salts represent a novel, highly reactive class of acetylenic iminium salts. Herein we present several reactions which are based on the electron-poor acetylenic bond and on the high electrophilicity of the CF3-substituted iminium group. These salts were found to be highly reactive dienophiles in Diels–Alder reactions with cyclopentadiene, 2,3-dimethylbutadiene and even anthracene. At higher temperature, the cycloadducts undergo an intramolecular SE(Ar) reaction leading to condensed carbocycles incorporating a 1-(trifluoromethyl)-1-(dimethylamine)indene ring system. With styrenes and some substituted styrenes, cascade reactions take place, which likely include cyclobutene and several cationic intermediates and mainly yield 2-(1-phenylvinyl)indenes. In a similar reaction cascade, a fulvene derivative was obtained with 1,4-diphenylbutadiene as the substrate.
Keywords: alkynes; aromatic substitution; cyclization; cycloaddition; iminium salts